On Research of Pharmacological Activity of "Bioil", Polyunsaturated Fatty Acids Concentrate (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: reparative; anti-inflammatory; polyunsaturated fatty acids; â€œbioilâ€.